1995
DOI: 10.1095/biolreprod52.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Melengestrol Acetate at Greater Doses than Typically Used for Estrous Synchrony in Bovine Females Does not Mimic Endogenous Progesterone in Regulation of Secretion Of Luteinizing Hormone and 17β-Estradiol1

Abstract: Our working hypothesis was that doses of melengestrol acetate (MGA) greater than those typically administered in estrous synchrony regimens would regulate secretion of LH and 17 beta-estradiol (E2) as endogenous progesterone (P4) does during the midluteal phase of the estrous cycle. We also hypothesized that endogenous P4 from the CL would interact with MGA to further decrease the frequency of LH pulses and E2. Cows on Day 5 of their estrous cycle (Day 0 = estrus) were randomly assigned to an untreated control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…In a recent study (Custer et al 1994), the dominant follicle persisted in 10 of 23 cattle treated with MGA for 7 d, starting on day 17 of the cycle; the low plasma progestagen concentrations in MGA-treated cattle without a functional corpus luteum resulted in increased LH pulse frequencies but insufficient LH release to cause ovulation (Kojima et al 1995). Following cessation of MGA treatment, ovulation occurred with an aged oocyte from the persistent follicle (Custer et al 1994).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a recent study (Custer et al 1994), the dominant follicle persisted in 10 of 23 cattle treated with MGA for 7 d, starting on day 17 of the cycle; the low plasma progestagen concentrations in MGA-treated cattle without a functional corpus luteum resulted in increased LH pulse frequencies but insufficient LH release to cause ovulation (Kojima et al 1995). Following cessation of MGA treatment, ovulation occurred with an aged oocyte from the persistent follicle (Custer et al 1994).…”
Section: Discussionmentioning
confidence: 97%
“…However, this hypothesis was not supported. In a recent study (Kojima et al 1995) reported after completion of exp. 1, it was shown that 1 mg d -1 MGA was unable to suppress LH pulse frequency, and as a result follicular size and plasma estrogen concentrations increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies (Macmillan et al 1991;Van Cleef et al 1991), progesterone treatment after breeding improved pregnancy rates, although the increase was significant only when pregnancy rates in untreated cattle were relatively low. Perhaps progesterone would be more efficacious, as it causes more profound suppression of the hypothalamicpituitary axis than MGA (Kojima et al 1995) and therefore may be more effective for sustaining pregnancy. Another alternative is hCG, which has improved pregnancy rates when injected a few days after breeding (Walton et al 1990;Sianangama and Rajamahendran 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This regimen effectively synchronizes estrus, but pregnancy rates are lower in cattle that are late in the estrous cycle at the start of MGA treatment compared with those that are early. When this regimen is started late in the estrous cycle, the corpus luteum regresses, a dominant ovarian follicle becomes large and persists, and plasma estrogen concentrations increase (Custer et al 1994;Kojima et al 1995). This regimen has been recently modified to include treatment with 5 mg E17β (and 100 mg progesterone) on day 1 (Kastelic et al 1996).…”
Section: Mots Clésmentioning
confidence: 99%